The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11892-010-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Analogues in the Management of the Pregnancy Complicated by Diabetes Mellitus

Abstract: Since their introduction, insulin analogues are the preferred choice for short-acting insulin due to their superior pharmacologic profiles, leading to greater flexibility and convenience of dosing and, thus, greater patient satisfaction and improved quality of life. Over the past few years, clinical experience with insulin analogues in pregnancy has increased. The most studied, insulin lispro, has been shown to be a safe and clinically effective option in the treatment of the diabetic gravida. Studies of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Another change in recent years has been the use of rapid-acting insulin analogues instead of human insulin. It is unlikely, however, that this could have resulted in the trend for increased HbA 1c since rapid-acting insulin analogues are equally effective [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another change in recent years has been the use of rapid-acting insulin analogues instead of human insulin. It is unlikely, however, that this could have resulted in the trend for increased HbA 1c since rapid-acting insulin analogues are equally effective [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reviews [5][6][7] surveyed clinical studies for comparisons of fetal overgrowth between RI and insulin analogs, including LP, in pregnancies complicated by diabetes. These qualitative reviews concluded that overall there were no relevant differences in rates of neonatal macrosomia and LGA between LP and RI treatment groups.…”
mentioning
confidence: 99%
“…10,11 Although based on unadjusted analyses, observational studies in pregnant patients also found benefits of LP over RI, with better glycemic control 4,7,12 and less hypoglycemia. 4,7 A fuller assessment of the risks and benefits of LP remains to be studied in pregnant insulintreated patients with diabetes.…”
mentioning
confidence: 99%
“…Edson-Heredia et al 1 point out that recent literature reviews [5][6][7] concluded that there were no relevant differences in rate of macrosomia and LGA, but we would like to underscore that all of them are qualitative reviews. The difference is that we performed a systematic review and meta-analysis.…”
mentioning
confidence: 89%